A study of hydrothermally grown ZnO nanorod-based metal-semiconductor-metal UV detectors on glass substrates. (10th April 2017) - Singh, Shaivalini; Kumar, Yogesh; Kumar, Hemant; Vyas, Sumit; Periasamy, Chinnamuthan; Chakrabarti, Parthasarathi; Jit, Satyabrata; Park, Si-Hyun
This study reports hydrothermally grown zinc oxide nanorod-based metal-semiconductor-metal ultraviolet detectors with palladium metal as the electrodes. The zinc oxide nanorods were deposited on glass substrates in two steps, seed layer deposition and growth of nanorods. The structural and optical properties of nanorods were examined using scanning electron microscopy and ultraviolet–vis spectroscopy, respectively. The scanning electron microscopy image showed that the growth of nanorods was uniform, and the ultraviolet–vis results indicate that the bandgap of zinc oxide nanorods was 3.23 eV. For metal-semiconductor-metal devices, interdigited metal electrodes with equal interelectrode spacing and a width of 0.3 mm were deposited above the zinc oxide nanorod thin films with a shadow mask using a thermal evaporation system. The current–voltage characteristics of the metal-semiconductor-metal detector were investigated and it showed a contrast ratio of approximately 2.10 and responsivity of approximately 0.199 A/W at 1.8 V. These results are expected to be beneficial to fabricating cheap and practical ultraviolet detection applications.